Reimagining GO and SEND Mission Paradigms for an Age of Global Migration and World Christianity - George, Sam (International bulletin of mission research, 2023)
I interrogate the principal mission terms GO and SEND from post-Christendom, post-Western, and World Christianity perspectives, considering our increasingly globalized and polarized world and the emerging context of twenty-first-century Christianity. This approach exposes some of the inherent bias in mission thinking and calls for a perspectival shift toward bidirectionality and polycentrism, as the missionary impetus can now originate anywhere and result anywhere else in the world. Christian mission is no more from the West to the Rest but increasingly from everywhere to everywhere, which requires a new consideration of dispersion and reciprocity that is embedded within a multipolar world.